STABILITAS POOLED SERA BERDASARKAN LAMA DAN SUHU PENYIMPANAN TERHADAP MUTU PEMERIKSAAN PROTEIN TOTAL - indah sari (Masker Medika, 2024)
Introduction: internal quality stabilization in clinical chemistry laboratory can be carried out by conducting serum control examination which aims to test or assess the validity of laboratory examination results and the results issued by the laboratory in accordance with the criteria of the examination results. The use of pooled sera made from the remaining patient specimens can be an alternative to reduce the cost of quality control of laboratory examinations. Total protein levels in the blood can be determined by examination in a clinical laboratory as an indicator of protein status in the body. A common problem in clinical laboratories is maintaining the stability of serum analytes during sample storage. Purpose of the study: to determine the stability of pooled sera based on the duration and storage temperature of the quality of the total protein examination. Method: the type of research is experimental, with the design of the study is time series control group design. The sample in this study was a control serum in the form of pooled sera stored in a freezer that was examined for total protein every day for 4 weeks. Results: mean total protein test was 6.1 mg/dl in commercial control and 6.6 mg / dl in pooled sera. Discussion: there is an effect of long storage in the freezer on the stability of total protein examination.